A Competitive Efficiency Wage Model with Keynesian Features - Kahn, Charles; Mookherjee, Dilip (Quarterly Journal of Economics, 1988)
We study a general equilibrium efficiency wage model characterized by fully optimizing agents, flexible prices, and imperfect information. The model has a unique competitive equilibrium with underemployment in a sector (called manufacturing) with efficiency wages, relative to a self-employment sector. Since prices are flexible, the multiplier of manufacturing output with respect to autonomous demand changes may or may not exceed unity: demand changes lead to price effects as well as income effects that work opposite each other. Nevertheless, there always exist government policies that achieve Pareto improvements by switching demand toward the manufacturing sector. Optimal demand-switching policies are explicitly characterized.